The Marrying Kind? : Debating Same-Sex Marriage within the Lesbian and Gay Movement - Bernstein, Mary (Book collections on Project MUSE., 2013)
As the fight for same-sex marriage rages across the United States and lesbian and gay couples rush to marriage license counters, the goal of marriage is still fiercely questioned within the LGBT movement. Rarely has an objective so central to a social movement's political agenda been so controversial within the movement itself. While antigay forces work to restrict marriage to one man and one woman, lesbian and gay activists are passionately arguing about the desirability, viability, and social consequences of same-sex marriage. The Marrying Kind? is the first boo.